Madrasah Relevance Management Efforts and the Digital Era (Study at MI Miftahul Ulum Banggle 02 Kanigoro Blitar and MI Al Muhajirin II Latukan Karanggeneng Lamongan) - Latif Syaipudin; Akhyak, Akhyak; Abd. Aziz (International Journal of Management Science, 2024)
Digitalization and madrasah educational institutions are subjects and objects that are interrelated in the development of digital education. An educational institution cannot escape the changes that occur, this is an inevitability in the field of education that cannot be separated. This research approach uses qualitative, with the research object being MI Miftahul Ulum Banggle 02 Kanigoro Blitar and MI Al Muhajirin II Latukan Karanggeneng Lamongan. The results of this research show that there are several important aspects that must be considered, namely: 1) The development of the digital era, where the digital era is a change that must be followed by various educational institutions, because this is an era change that must be followed. 2) Renewing digital platforms for developing educational models, at this point an educational institution must have the courage to utilize the available digital platforms as learning models. 3) Technology in social change for education in principle is that technology will have a broad impact, especially the occurrence of social change in society. 4) The development of the digital era in the scope of Islamic education, as with social changes, will also be affected in the scope of Islamic education levels. So the importance of strong management in managing the changes that occur.